2016
DOI: 10.1037/tra0000102
|View full text |Cite
|
Sign up to set email alerts
|

Treatment decision-making for posttraumatic stress disorder: The impact of patient and therapist characteristics.

Abstract: Taken together, these results suggest that providers are increasingly likely to view exposure-based EBPs for PTSD as effective, and that continued dissemination efforts to increase provider familiarity and comfort with these protocols will likely improve rates of EBP use across a variety of practice settings. (PsycINFO Database Record

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 36 publications
4
33
0
Order By: Relevance
“…It was acknowledged, however, that trauma focused interventions, irrespective of whether the individual has a co-morbid psychosis diagnosis or not, can lead to distress (Devilly and Spence, 1999), and initial worsening of PTSD symptoms, emotional exhaustion and other physical symptoms of anxiety during the exposure phase of the treatment (Shearing et al, 2011; Hundt et al, 2016). No adverse events were reported in the majority of the studies.…”
Section: Discussionmentioning
confidence: 99%
“…It was acknowledged, however, that trauma focused interventions, irrespective of whether the individual has a co-morbid psychosis diagnosis or not, can lead to distress (Devilly and Spence, 1999), and initial worsening of PTSD symptoms, emotional exhaustion and other physical symptoms of anxiety during the exposure phase of the treatment (Shearing et al, 2011; Hundt et al, 2016). No adverse events were reported in the majority of the studies.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that not only patient-related characteristics, such as comorbidity (Becker et al, 2004; van Minnen et al, 2010), but also therapist-related factors, are strongly related to the underuse of TFTs (Harned, Dimeff, Woodcock, & Contreras, 2013; Hundt, Harik, Barrera, Cully, & Stanley, 2016; Laska, Smith, Wislocki, Minami, & Wampold, 2013), such as therapists’ negative beliefs or expectations about the application of TFT (N. R. Farrell, Deacon, Kemp, Dixon, & Sy, 2013; Meyer, Farrell, Kemp, Blakey, & Deacon, 2014; van Minnen et al, 2010) or therapists’ own anxiety sensitivity (Meyer et al, 2014), indicating that some therapists may simply be afraid to conduct this type of therapy. In addition to these hesitations to start a TFT, during the TFTs some therapists drift from the protocol (Waller, 2009) or deliver their (exposure) treatment in a suboptimal way, for instance by using anxiety-diminishing techniques (Hipol & Deacon, 2013), avoiding encouraging patients to carry out exposure exercises that elevate high levels of anxiety, or avoiding the application of (therapist-assisted) exposure in vivo during the treatment sessions (N. R. Farrell et al, 2013; Hipol & Deacon, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that positive experiences with using exposure reduced initial therapist fears and insecurities, which is in accordance with the findings of Eftekhari et al (45), who found that experiences of success encourage further use of this technique. A significant effect of positive experience of application was also found by Hundt et al (39), who ascertained that behavioural-cognitive therapists who are younger and have less experience but frequently treat patients with PTSD are more likely to choose empirically proven treatments such as exposure therapy. The authors conclude that greater knowledge of protocol and more confidence in the therapist's own competences increase their readiness to recommend and use exposure therapy.…”
Section: Discussionmentioning
confidence: 57%
“…Although almost all therapists required an insurance cover from an insurance agency for the use of exposure in their work with patients with obsessive-compulsive disorder, over 80% of patients reported that not a single form of exposure was used during treatment. Also, despite evidence that effective treatment for post-traumatic stress disorder include prolonged exposure, studies have shown that only 6-13% of veterans seeking help for PTSD receive empirically proven treatments (39), most often due to the fears of therapists and patients regarding the possibility of tolerating exposure therapy. Qualitative analysis of interviews with veterans who participated in eight exposure sessions showed that, despite initial worsening of symptoms, most veterans claimed that it was a positive and useful experience.…”
Section: Introductionmentioning
confidence: 99%